The Predictability of Routine Activity Theory for Cyberbullying Victimization Among Children and Youth: Risk and Protective Factors - Aizenkot, Dana (Journal of interpersonal violence, 2022)
Cyberbullying has been pervading worldwide with negative implications for victims. Therefore, there is an urgent need to better understand this phenomenon and the factors that predict it, as the basis for effective prevention and intervention efforts. The current research aims to examine routine activity theory (RAT) as a theoretical framework predictive of cyberbullying victimization (CV) among children and youth. It was hypothesized that each of the RAT measures and the convergence of all measures predict CV. Data were collected from 5,719 primary, middle, and high school Israeli students (51.9% females) during the 2019?2020 school year via online questionnaires. Regression and moderation analyses were conducted to assess the predictability of CV from RAT measures, separately and converged. All RAT measures, separately and converged, predict CV. While off-line trust negatively predicts CV, other control variables, that is, online trust, educational institution phase, and gender, do not. Implications for school programs and guidelines for parents address the risk and protective factors of CV found. This study provides support for the predictability of CV from RAT and expands the knowledge of risk and protective factors predictive of CV.